Community of Independent States as an Organization of Regional Security - S. I. Chernyavskiy (Проблемы постсоветского пространства, 2020)
The article analyzes the activities of the Commonwealth of Independent States as an organization of regional security. Despite the fact that after the collapse of the Soviet Union about 30 years have passed, the ruling elites of the New Independent States continue to search for their own vectors of foreign and defense policy. The author believes that in the pursuit of the many attributes of independence, these elites still have not defined clear boundaries for themselves where they can sacrifice national sovereignty for the benefit of their own development, but in close cooperation with their neighbors. The CIS, as an umbrella association of the post-Soviet republics, continues to be a platform for dialogue between the leaders of the new generation, not connected by the Soviet past. Their foreign policy is dominated by pragmatism and multivectorness. Therefore, the absence of a rigid managerial dominance in the Commonwealth is for them the key to the success of this regional format. It seems that this means that, using the CIS as a convenient and non-binding stage for communication, the participating states will continue to search for themselves the most profitable areas of cooperation, even if through trial and error. In such a context, the main areas of cooperation will remain the fight against terrorism and organized crime, as well as the use of Russian experience in reflecting new challenges and threats.